KOMIK DAKWAH SEBAGAI MEDIA EDUKASI ISU PALESTINA PADA AKUN INSTAGRAM @ANIMASITAARTS PRESPEKTIF EDUTAIMENT - Amalia, Rizky Amalia; Bakti, And Faisal; Mustopa, Desty Heppyani; Fitriyah, Ratu Maulidah; Halimah, Halimatus Sa'diyah (Holistik: Journal for Islamic Social Sciences, 2024)
The Israeli-Palestinian conflict is one of the most complex and protracted geopolitical issues in the world, marked by injustice, human rights violations, and a deep humanitarian crisis. Amid global efforts to find a peaceful solution, the dissemination of accurate information and education about the root causes and impacts of the conflict is crucial. This study examines the role of animation as a tool for social change, focusing on the Instagram account @animasitaarts, which actively promotes a movement for change through content about Palestine. It uses a constructivist paradigm and a transdisciplinary approach to communication, social, and religious studies. Qualitative research as a tool for social change, the potential for social mobilization, and the formation of collective action among @animasitaarts followers through Thomas Tuftte's edutainment theory from Jan Serveas' book (2008). The results of the study show that @animasitaarts' dakwah comics, with their attractive visuals and touching narratives, are effective in building positive reactions and audience awareness of the suffering in Palestine. Despite being limited to the Instagram platform, @animasitaarts has successfully become a prominent educational space within the da'wah community, encouraging digital solidarity actions such as praying and donating, and inspiring collective action as a form of concern for the Palestinian people. This indicates that animation, particularly through social media platforms such as Instagram, has great potential as an effective medium for da'wah and education on social and humanitarian issues, bridging the information gap and fostering collective awareness. Konflik Israel-Palestina merupakan salah satu isu geopolitik paling kompleks dan berkepanjangan di dunia, ditandai oleh ketidakadilan, pelanggaran hak asasi manusia, dan krisis kemanusiaan yang mendalam. Di tengah upaya global untuk mencari solusi damai, penyebaran informasi dan edukasi yang akurat mengenai akar masalah dan dampaknya menjadi krusialenelitian ini mengkaji peran animasi sebagai alat perubahan sosial, dengan fokus pada akun Instagram @animasitaarts yang secara aktif mendorong gerakan perubahan melalui konten dakwah tentang Palestina. Dengan menggunakan paradigma konstruktivisme dan pendekatan transdisiplin ilmu komunikasi, sosial dan dakwah. Penelitian kualitatif sebagai alat perubahan sosial, potensi mobilisasi sosial, dan pembentukan aksi kolektif di kalangan pengikut @animasitaarts melalui teori edutaiment Thomas Tuftte dari buku Jan Serveas (2008). Hasil penelitian menunjukkan bahwa komik dakwah @animasitaarts, dengan visualisasi menarik dan narasi yang menyentuh, efektif membangun reaksi positif dan kesadaran audiens terhadap penderitaan di Palestina. Meskipun terbatas pada platform Instagram, @animasitaarts berhasil menjadi ruang edukasi yang menonjol di kalangan komunitas dakwah, mendorong aksi solidaritas digital seperti berdoa dan berdonasi, serta menginspirasi aksi kolektif sebagai wujud kepedulian terhadap rakyat Palestina. Hal ini mengindikasikan bahwa animasi, khususnya melalui platform media sosial seperti Instagram, memiliki potensi besar sebagai medium dakwah dan edukasi yang efektif untuk isu-isu sosial dan kemanusiaan, menjembatani kesenjangan informasi dan mendorong kesadaran kolektif